Clap your hands - Cauley, Lorinda Bryan. (Putnam, 1992)
Rhyming text instructs the listener to find something yellow, roar like a lion, give a kiss, tell a secret, spin in a circle, and perform other playful activities along with the human and animal characters pictured.
On board pages.
Cover title.
Rhyming text instructs the listener to find something yellow, roar like a lion, give a kiss, tell a secret, spin in a circle, and perform other playful activities along with the human and animal characters pictured.
Keywords: Stories in rhyme.; Animals / Fiction.; Play / Fiction.